International Journal of Civil Engineering and Tecnology (IJCIET) - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
International Journal of Civil Engineering and Tecnology (IJCIET)